Silver powder, method for producing the same, and conductive paste
By adhering the metal oxide with low melting point to the surface of the silver particles, the problem of insufficient bonding strength between the conductive paste and the substrate in the conductive paste is solved, and the stability and conductivity of the high aspect ratio conductive pattern are improved.
Patent Information
- Application Number
- CN202180016524.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-26
- Filing Date
- 2021-03-24
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-03-24
AI Technical Summary
The conventional conductive paste cannot improve the bonding strength between the conductive pattern and the substrate when forming the conductive pattern, resulting in electrode peeling easily in the conductive pattern with a high aspect ratio.
By adhering the metal oxide at a low melting point to the surface of the silver particles, the uneven presence of the silver particles and the metal oxide powder at a low melting point is suppressed, thereby improving the bonding strength of the conductive pattern.
It is achieved to reduce electrode peeling in the conductive pattern with a high aspect ratio, and improve the bonding strength and strength of the conductive pattern.
Smart Images

Figure CN115175777B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to silver powder, a method for producing the same, and a conductive paste. Background Art
[0002] In recent years, conductive pastes using silver powder have been required to have higher density of conductor patterns and thinner wiring due to miniaturization of electronic components. In addition, thinning of finger electrodes is also required to increase the light collecting area of solar cells and improve power generation efficiency.
[0003] As a conductive paste, for example, a scheme containing low melting point metals such as metallic tellurium and tellurium oxide as additives has been proposed (for example, refer to Patent Document 1). By containing a low melting point metal, the contact resistance can be improved, for example, when forming an electrode of a solar cell. A low melting point metal refers to a metal having a melting point of 500°C or less, for example, zinc (melting point 419.6°C), lead (melting point 327.5°C), tin (melting point 231.97°C), bismuth (melting point 271.3°C), tellurium (melting point 449.5°C), and selenium (melting point 217°C). Furthermore, it is believed that a substance having a melting point below the baking temperature of the conductive paste (a low melting point metal compound such as tellurium dioxide) or a substance that causes a chemical reaction (physical change) at a temperature below the baking temperature of the conductive paste can be used instead of the low melting point metal.
[0004] Furthermore, for example, a conductive paste containing a tellurium alloy compound such as silver telluride as an additive has been proposed (see, for example, Patent Document 2).
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2010 / 016186
[0008] Patent Document 2: Japanese Patent Application Publication No. 2018-190967 Summary of the invention
[0009] Problem that the invention aims to solve
[0010] However, in order to reduce the ground area and suppress the conductor resistance while increasing the density of conductor patterns and reducing the wiring thickness, it is required to increase the electrode height (aspect ratio) relative to the ground width.
[0011] In addition, in order to improve the reliability of the conductive pattern, it is necessary to obtain a high bonding strength between it and the substrate. For example, in the case of a solar cell, electrode peeling of finger electrodes and busbar electrodes becomes a problem, and for these electrodes, it is required to obtain a high bonding strength between them and the Si surface or SiN surface as the substrate.
[0012] However, in the conductive pastes of Patent Documents 1 and 2, the bonding strength between the conductive pattern and the base cannot be increased, and therefore, when the aspect ratio of the conductive pattern is increased, electrode peeling may be easily caused.
[0013] An object of the present invention is to provide silver powder that can provide high bonding strength when forming a conductive pattern, a method for producing the same, and a conductive paste containing the same.
[0014] Solutions for solving problems
[0015] The present inventors have studied the problem that the bonding strength of the conductive pattern cannot be improved when the conductive paste contains both silver particles and low-melting-point metal oxide powder. They believe that the decrease in bonding strength is due to the difference in specific gravity between silver and metal oxide powder. The specific gravity of the low-melting-point metal oxide is smaller than that of silver (about 10.5 g / cm 3 ). In the conductive paste, silver powder and metal oxide powder can move freely. Therefore, before or after applying the conductive paste, there is a concern that those with higher specific gravity and those with lower specific gravity aggregate with each other, and silver particles and metal oxide powder are unevenly present.
[0016] There are metal oxides that have the effect of reducing the softening point temperature of the glass powder mixed in the conductive paste. Due to the decrease in the softening point temperature of the glass powder, when the coating film is baked, the glass flows quickly, moves to the interface between the film and the substrate before the silver is sintered, and forms a strong bond to ensure the adhesion strength. If the uneven presence of metal oxides is generated here, it is predicted that the softening point temperature of the glass will be uneven, and the softening point reduction effect will not be effectively exerted. Furthermore, since the film interior of the conductive pattern after baking becomes uneven, the contact points of different phases become the starting point, and the possibility of film destruction becomes larger. It is believed that if the metal oxide is dispersed in the film interior, the starting point of the film destruction caused by the unevenness is reduced, which helps to improve the strength improvement of the conductive pattern.
[0017] Therefore, the present inventors have studied methods for suppressing uneven existence of silver particles and low-melting-point metal oxide powder, and focused on a method of preliminarily adhering low-melting-point metal oxide as an adherend to the surface of silver particles with a high specific gravity. It has been found that by adhering low-melting-point metal oxide to silver particles in this way, even if silver powder is mixed in a conductive paste, uneven existence of low-melting-point metal oxide caused by a specific gravity difference can be suppressed, and the bonding strength of the conductive pattern can be improved. As a result, even when a conductive pattern is formed with a high aspect ratio, electrode peeling can be reduced.
[0018] The invention made based on the above findings is the following aspects.
[0019] A first aspect of the present invention is a silver powder having:
[0020] Silver particles; and, an adherent adhered to the surface of the silver particles and comprising a metal oxide having a melting point lower than that of silver.
[0021] A second aspect of the present invention is the first aspect,
[0022] The metal oxide is at least one of Te oxide, Bi oxide, Pb oxide, Tl oxide and V oxide.
[0023] A third aspect of the present invention is the first or second aspect,
[0024] The content of the metal component constituting the metal oxide is 0.01% by mass to 10% by mass based on silver.
[0025] A fourth aspect of the present invention is any one of the first to third aspects,
[0026] When the metal oxide is used as the first adherend, the adherend includes a second adherend containing a metal formed of a metal component constituting the metal oxide or an alloy of the metal component and silver.
[0027] A fifth aspect of the present invention is the fourth aspect,
[0028] The metal component is at least one of Te, Bi, Pb, Tl, and V.
[0029] A sixth aspect of the present invention is any one of the first to fifth aspects,
[0030] The total amount of metal components other than silver constituting the metal oxide in the adhered material is 0.1% by mass to 10% by mass based on silver.
[0031] A seventh aspect of the present invention is a method for producing the silver powder of the first aspect, comprising the following steps:
[0032] A reducing agent and an aqueous solution containing a metal component constituting a metal oxide having a melting point lower than that of silver are added to the silver complex solution.
[0033] The silver particles are reduced and precipitated, and the metal oxide of the metal component is precipitated and adhered on the surface of the silver particles.
[0034] An eighth aspect of the present invention is a conductive paste including:
[0035] Silver powder of the first to sixth aspects; silver powder having no adherent matter containing metal on the surface; organic binder; glass powder; and solvent.
[0036] A ninth aspect of the present invention is the eighth aspect,
[0037] The content of the metal component constituting the metal oxide contained in the silver powder of the first to sixth aspects is 0.001 mass % to 0.03 mass % based on the silver contained in the conductive paste.
[0038] Effects of the Invention
[0039] High bonding strength can be obtained when forming a conductive pattern. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is a diagram showing element mapping of the surface of the silver powder of Example 1.
[0041] Figure 2 This is a diagram showing element mapping of a cross section of the silver powder of Example 1.
[0042] Figure 3 3 is a diagram showing element mapping of the surface of the silver powder of Example 4.
[0043] Figure 4 This is a diagram showing element mapping of a cross section of the silver powder of Example 4.
[0044] Figure 5 1 is a diagram showing element mapping of the cross section of each conductor pattern of Example 1, Comparative Example 2, and Comparative Example 3. DETAILED DESCRIPTION
[0045] <One embodiment of the present invention>
[0046] Hereinafter, one embodiment of the present invention will be described. It should be noted that in this specification, "silver particles" is an expression when focusing on individual silver particles, and "silver powder" is an expression when treating a plurality of silver particles as an aggregate. In addition, a numerical range expressed using "to" means a range including the numerical values recorded before and after "to" as the lower limit and upper limit.
[0047] (Silver powder)
[0048] Silver powder is mixed in a conductive paste for forming conductive patterns such as electrodes and circuits in electronic components (such as solar cells, etc.). The silver powder of this embodiment comprises silver particles and an adherent adhering to the surface of the silver particles and containing a metal oxide having a melting point lower than that of silver, and is a metal oxide adhered silver powder.
[0049] The adhesive contains a metal oxide having a melting point lower than that of silver. The adhesive reduces the softening point of the glass powder during the sintering process of the conductive paste. By reducing the softening point of the glass, the glass can be facilitated to flow before the silver is sintered, and the glass can flow evenly to the interface between the coating film and the substrate. As a result, microcracks in the conductor pattern after firing can be reduced to improve the strength, and the bonding strength between the conductor pattern and the substrate can also be improved.
[0050] The adherent is arranged to adhere to the silver particles in a manner covering a part or all of the surface of the silver particles. Preferably, the adherent can be dispersed and distributed on the surface of the silver particles in a manner covering a part of the surface of the silver particles. Here, adhesion refers to a state of being more firmly attached to the surface of the silver particles than simple adhesion. In the case where the silver powder and the powder of the low-melting-point metal oxide are simply mixed, even if it is assumed that the metal oxide powder is attached to the surface of the silver particles, the metal oxide powder and the silver particles are easily separated. In this embodiment, as described later, when the silver particles are reduced and precipitated, the low-melting-point metal oxide is precipitated in a manner adhering to the surface of the silver particles. Therefore, the adhesion strength of the adherent to the silver particles can be set to, for example, the following strength: even if the metal oxide adhered silver powder is broken, the adherent will not detach from the surface of the silver particles. Thus, even when the metal oxide adhered silver powder is kneaded in the conductive paste, the adherent and the silver particles can exist at the same time. That is, the uneven existence of the silver particles and the low-melting-point metal oxide can be suppressed.
[0051] The adherent contains a metal oxide. The metal oxide is not particularly limited as long as the melting point is lower than that of silver, and preferably includes tellurium (Te) oxide, bismuth (Bi) oxide, lead (Pb) oxide, thallium (Tl) oxide, and vanadium (V) oxide. Examples of Te oxide, Bi oxide, Pb oxide, Tl oxide, and V oxide are TeO 2 (melting point 733℃), B 2 O 3 (melting point 817℃), PbO 2 (melting point 223℃), Pb 3 O 4 (melting point 686°C), PbO (melting point 290°C), Tl 2 O 3 (melting point 717℃), V 2 O 5 (melting point 690°C), which is lower than the melting point of silver (962°C). Among them, tellurium (Te) oxide or bismuth (Bi) oxide is particularly preferred. According to these oxides, the softening point temperature of the glass powder added to the conductive paste can be lowered. As a result, for example, when the conductive paste is baked, it becomes easy to fill the gaps between the silver particles with molten glass, which can promote the adhesion and fusion between the silver particles. As a result, the strength of the conductor pattern can be improved. Moreover, the contact resistance of the conductor pattern can be reduced by burn-through.
[0052] When the above-mentioned metal oxide is used as the first adherend, the adherend of this embodiment may include a second adherend different from the first adherend. The second adherend includes: a metal formed by a metal component constituting the metal oxide in the first adherend or an alloy of the metal component and silver. If the metal oxide in the first adherend includes Te oxide, Bi oxide, Pb oxide, Tl oxide, V oxide, the second adherend may include a metal single substance of Te, Bi, Pb, Tl, V, or an alloy thereof with silver. For example, if the first adherend includes Te oxide, the second adherend may include a Te metal single substance or an Ag-Te alloy. Furthermore, the adherend may include both the metal oxide and silver, or may be in an amorphous state of the metal oxide and silver.
[0053] On the surface of the silver particles, the ratio of the first adherend to the second adherend is preferably 1:9 to 10:0 (the ratio of the first adherend is 10 to 100%), and more preferably 1:9 to 9:1 (the ratio of the first adherend is 10 to 90%). Here, the ratio of the first adherend to the second adherend represents the ratio of the number of atoms of the metal component constituting each adherend. If there is a second adherend, the adhesion between the first adherend and the surface of the silver particles can be further enhanced. The ratio of the number of atoms of the metal component constituting the metal oxide in the first adherend to the metal component (excluding silver in the alloy) in the second adherend is measured based on the state analysis results of the silver particle surface using ESCA. In ESCA, for a sample where silver particles are densely present, the analysis area is set to, for example, 800 μmφ for measurement, and the surface of a plurality of silver particles (for example, more than 100) can be measured.
[0054] It should be noted that tellurium is a semi-metal element, but in this specification, for convenience, it is not distinguished from other metal elements and is collectively referred to as a metal, a metal component, or a metal in a metal oxide.
[0055] In the metal oxide adhered silver powder, the total amount of metal components other than silver constituting the metal oxide in the adherend is preferably 0.1 mass % to 10 mass % relative to the silver contained in the metal oxide adhered silver powder. It can be more preferably set to 0.1 mass % to 3 mass %. Here, for the metal components other than silver constituting the metal oxide, for example, if the adherend is formed by a metal component, or the adherend is an amorphous state of metal oxide and silver, the content of the metal component constituting the metal oxide is indicated. And, for example, if the adherend includes the first adherend and the second adherend, it indicates the addition of the content of the metal component constituting the metal oxide in the first adherend and the metal component (excluding silver in the alloy) in the second adherend. Moreover, when the adherend includes the first adherend and the second adherend, the ratio of the metal component constituting the metal oxide in the first adherend to the total amount of the metal component is preferably 10 to 100%, and the amount of the metal component constituting the metal oxide is preferably 0.01% to 10% by mass, more preferably 0.01% to 9% by mass, and further preferably 0.1% to 3% by mass relative to the silver contained in the metal oxide adhered silver powder. By making the content of the metal component constituting the metal oxide more than 0.01% by mass relative to silver, the effect of the low melting point metal oxide can be more reliably obtained. On the other hand, if the content of the low melting point metal oxide is excessively increased, the resistance of the conductive pattern becomes large and the conductivity is sometimes impaired. In this regard, by making the content less than 10% by mass relative to silver, the effect of the low melting point metal oxide can be obtained, and the conductivity of the conductor pattern can be maintained at a high level.
[0056] It should be noted that the total amount of silver contained in the metal oxide adhered silver powder, the metal component constituting the metal oxide in the first adherend, and the metal component other than silver in the second adherend can be measured as follows. First, the silver content can be measured by a weight method (mass method), that is, after the metal oxide adhered silver powder is completely dissolved in nitric acid, hydrochloric acid is added to precipitate silver chloride and filtered, and the mass of the silver chloride is measured. The total amount of the metal component constituting the metal oxide in the first adherend and the metal component in the second adherend can be measured by heating and dissolving the metal oxide adhered silver powder in nitric acid, and then completely dissolving it with aqua regia or the like as needed, and then using inductively coupled plasma (ICP) emission spectrometry analysis or the like. It should be noted that, in the present embodiment, since Te oxide dissolves together with Te in nitric acid, the first adherend and the second adherend are measured without distinction using nitric acid as described above. However, in the case where the metal oxide is not completely dissolved in nitric acid and can be recovered as a precipitate, the amount of the metal component constituting the metal oxide in the first adherend can be measured based on the amount of the metal oxide recovered by solid-liquid separation, and the amount of the metal component other than silver in the second adherend can be measured based on the filtrate.
[0057] The particle size of the metal oxide adhered silver powder is not particularly limited, and the cumulative 50% particle size (D50) based on volume is preferably 0.5 μm to 4 μm. For the particle size distribution, 0.1 g of silver powder can be dispersed in isopropyl alcohol (IPA), stirred for 2 minutes in a cell crusher (model: BM-4) manufactured by Nippon Seiki Seisaku-sho, and then measured using a laser diffraction particle size distribution measuring device (Microtrac MT3300EXII manufactured by Nikkiso Co., Ltd.). It should be noted that the shape of each particle in the metal oxide adhered silver powder is not particularly limited, and may be, for example, spherical, ellipsoidal, scaly, or indefinite in shape. The specific surface area of the metal oxide adhered silver powder based on the BET1 point method is not particularly limited, and may be, for example, preferably 0.45 to 1.2 m 2 / g.
[0058] (Method for producing silver powder)
[0059] Next, a method for producing the metal oxide-adhered silver powder will be described.
[0060] First, a silver complex solution for forming silver particles is prepared. The silver complex solution can be prepared, for example, by adding a complexing agent to an aqueous solution containing silver ions to generate a silver complex. Examples of the silver complex aqueous solution include silver-amine complex aqueous solutions.
[0061] As the supply source of silver ions, known sources can be used. For example, inorganic silver salts such as silver nitrate, silver sulfate, silver carbonate, silver chloride, and silver oxide can be used. The silver ion concentration in the aqueous solution is preferably 0.1% to 10% by mass at the stage before adding the reducing agent described later.
[0062] As the complexing agent of silver ion, for example, complexing compounds such as ammonium ions such as ammonia, ammonium salts, and salts of ethylenediaminetetraacetic acid (EDTA) can be used. Wherein, from the aspect that it is easy to form complex with silver ion, easy to clean, and impurities are not easy to remain, preferred ammonium ion. If ammonium ion is used as complexing agent, silver-amine complex is formed in aqueous solution. At this time, the coordination number of amine complex is 2, therefore, more than 2 moles of ammonium ions can be added relative to every 1 mole of silver ion.
[0063] In addition, a reducing agent is prepared for reducing the silver complex to precipitate the silver particles. As the reducing agent, those known in the past can be used. For example, organic substances such as formalin, ascorbic acid, hydrazine, alkanolamine, hydroquinone, oxalic acid, formic acid, aldehydes, alcohols, sugars, lower oxides of metals, sodium borohydride, etc. can be used. Among them, from the aspect of stable reactivity and rapid reduction of silver, ascorbic acid, glucose, formaldehyde, hydrazine and hydrazine carbonate are preferred, and formaldehyde, hydrazine and hydrazine carbonate are more preferred. The reducing agent can be used alone or in combination of two or more.
[0064] Moreover, in the present embodiment, in order to form an adherent containing a metal oxide having a melting point lower than that of silver on the surface of the silver particles, an aqueous solution containing a metal component constituting a metal oxide having a melting point lower than that of silver (that is, a metal component that forms a metal oxide having a melting point lower than that of silver when oxidized) is prepared. Specifically, the aqueous solution containing the metal component can be prepared by, for example, dissolving an inorganic salt such as an oxide or nitrate of a metal selected from Te, Bi, Pb, Tl, and V in water. The aqueous solution becomes acidic or alkaline by dissolving the inorganic salt containing the metal component. From the viewpoint of not significantly changing the pH of the silver complex aqueous solution, the aqueous solution preferably has a pH of 9 or more and is alkaline. In the case where the aqueous solution is acidic when the inorganic salt containing the metal component is dissolved, the pH can be adjusted to 9 or more by adding an alkaline solution such as NaOH in advance before reduction.
[0065] Next, a reducing agent and an aqueous solution containing the metal component are added to the silver complex solution. By adding the reducing agent, the silver particles are reduced and precipitated from the silver complex. In addition, by adding the aqueous solution containing the metal component, the metal is precipitated on the surface of the precipitated silver particles, and an adherent containing the oxide of the metal can be formed. Thus, a slurry containing metal oxide-adhered silver powder is obtained.
[0066] The amount of the reducing agent added is not particularly limited, but is preferably 1 equivalent or more relative to silver from the viewpoint of increasing the yield of silver.
[0067] As a method for adding the reducing agent, from the viewpoint of suppressing the aggregation of the metal oxide adhered to the silver powder after reduction precipitation, it is preferred to add the reducing agent at a rate of 1 equivalent / minute or more relative to the amount of silver ions. In addition, the reaction solution is preferably stirred during the period from the addition of the reducing agent to the completion of the reduction precipitation. In addition, the temperature of the reaction solution during the reduction is preferably set to 5°C to 80°C, and more preferably set to 5°C to 40°C.
[0068] The method of adding the aqueous solution containing the metal component can be carried out until the precipitation of the silver particles is completed after the reducing agent is added. In particular, the aqueous solution can be added during the period when the reducing power of the reducing agent added to the silver complex aqueous solution continues. For example, the aqueous solution can be added within a few seconds after the reducing agent is added. Moreover, for example, the reducing agent can be added after the aqueous solution is added to the silver complex aqueous solution in advance. On the other hand, if the addition of the aqueous solution is excessively slowed down after the addition of the reducing agent, the grain growth of the silver particles is prioritized, thereby hindering the precipitation of the metal component on the surface of the silver particles, and there is a concern that it will become impossible to form an adhesion.
[0069] In addition, a reducing agent and an aqueous solution containing a metal component are added to the silver complex solution, and after the metal oxide adheres to the silver powder and begins to precipitate, a reducing agent may be further added. By further adding a reducing agent, adhesion can be promoted.
[0070] A surface treatment agent may be added to the obtained slurry as needed. The surface treatment agent can maintain the dispersibility of the metal oxide adhering to the silver powder. As the surface treatment agent, for example, a conventionally known substance such as a fatty acid or a salt thereof can be used.
[0071] Next, the obtained slurry is filtered to recover the metal oxide-adhered silver powder. The recovered metal oxide-adhered silver powder is then washed with water. The water washing is preferably performed until the conductivity of the liquid after the water flow is less than 0.2 mS / m.
[0072] Next, the washed metal oxide adhered silver powder is dried, for example, by vacuum drying. The drying conditions may be, for example, 73° C. for 10 hours. By this drying, a dry powder is obtained. It should be noted that in the dry powder, part or all of the metal component contained in the adhered material may be oxidized.
[0073] Next, the obtained dry powder is crushed to obtain the metal oxide adhered silver powder of this embodiment. It should be noted that in the metal oxide adhered silver powder, the adhered matter adheres to the surface of the silver particles, so even if the metal oxide adhered silver powder is crushed, the detachment of the adhered matter can be suppressed.
[0074] (Conductive paste)
[0075] Next, the conductive paste will be described.
[0076] The conductive paste of this embodiment includes silver powder having the above-mentioned adherent material on the surface of silver particles (metal oxide adherent silver powder); silver powder having no adherent material containing metal on the surface; an organic binder; glass powder; and a solvent.
[0077] The silver powder having no metal-containing adherents on the surface is a silver powder having no first adherent or second adherent such as the metal oxide adherent silver powder on the surface, preferably excluding inevitable impurities in manufacturing and containing no metal components other than silver on the surface. The silver powder is mixed in the conductive paste to reduce the ratio of the metal oxide adherent silver powder in the conductive paste. Thus, the content of the metal component contained in the conductive paste can be reduced, the resistance of the conductive pattern can be reduced, and the conductivity can be improved. It should be noted that the silver powder having no metal-containing adherents on the surface can have a surface treatment agent such as fatty acid, which has been used for silver powder, adhered to its surface.
[0078] There is no particular limitation on the silver powder having no metal-containing adherent on the surface, and conventionally known ones can be used. In addition, the shape is also not particularly limited, and for example, various shapes such as spherical, flaky, resinous, and linear can be appropriately selected, and a variety of different shapes can be used in combination.
[0079] In the conductive paste, the addition ratio of the metal oxide adhered silver powder and the silver powder having no adherent containing metal on the surface is not particularly limited, but the content of the metal component derived from the adherent in the metal oxide adhered silver powder is preferably set to an addition ratio of 0.001 mass % to 0.03 mass % relative to the total amount of silver in the conductive paste.
[0080] As the organic binder, known resins can be used or resins can be dissolved in solvents. For example, cellulose derivatives such as methylcellulose, ethylcellulose, carboxymethylcellulose, polyvinyl alcohols, polyvinyl pyrrolidones, acrylic resins, alkyd resins, polypropylene resins, polyvinyl chloride resins, polyurethane resins, rosin resins, terpene resins, phenol resins, aliphatic petroleum resins, vinyl acetate resins, vinyl acetate-acrylate copolymers, butyral resin derivatives such as polyvinyl butyral can be cited. They can be used alone or in combination of two or more.
[0081] As the glass powder, it is preferred that the glass powder mainly contains a component selected from lead (Pb), tellurium (Te), lithium (Li), zinc (Zn), silicon (Si), aluminum (Al) and bismuth (Bi), and may contain sodium (Na), potassium (K), boron (B), tungsten (W), molybdenum (Mo), manganese (Mn), iron (Fe), vanadium (V), phosphorus (P), antimony (Sb), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), titanium (Ti), zirconium (Zr), lanthanum (La), etc. As other components, it should be noted that if the ICP analysis value is 0.1% by mass or more, it is recorded as "containing".
[0082] The glass powder can be appropriately selected according to the purpose of use of the conductive paste. For example, as a solar cell, it is preferred to use a glass powder called a Pb-Te-Bi system. The glass powder preferably moderately erodes the anti-reflection layer formed on the semiconductor layer of the solar cell, and adheres the baked product of the conductive paste, i.e., the silver electrode, to the semiconductor layer.
[0083] The solvent can be appropriately selected according to the purpose of use of the conductive paste. For example, one or more solvents can be selected from butyl carbitol acetate (BCA), butyl carbitol (BC), ethyl carbitol acetate (ECA), ethyl carbitol (EC), hexane, toluene, ethyl cellosolve, cyclohexanone, butyl cellosolve, butyl cellosolve acetate, diethylene glycol diethyl ether, diacetone alcohol, terpineol, methyl ethyl ketone, benzyl alcohol, methyl ethyl ketone, methyl isobutyl ketone, tetradecane, tetralin, propanol, isopropanol, dihydroterpineol, dihydroterpineol acetate, ethyl carbitol, 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate (Texanol), etc. and used. It should be noted that the content of the solvent is preferably 1 to 40% by mass relative to the conductive paste.
[0084] In addition to the above-mentioned components, other components may be appropriately blended into the conductive paste as required. Examples of other components that can be used include surfactants, dispersants, rheology modifiers, silane coupling agents, and ion trapping materials.
[0085] <Effects of the present embodiment>
[0086] According to this embodiment, one or more of the following effects can be achieved.
[0087] As a comparison, for example, when silver powder and metal oxide powder having a melting point lower than silver are added to the conductive paste, when applied to the substrate, the ones with higher specific gravity and the ones with lower specific gravity aggregate and exist unevenly, and the metal oxide powder exists unevenly. If the coating film in such an uneven state is fired, the softening point temperature of the glass powder is uneven, and the film itself becomes uneven. Therefore, the contact points between different phases become starting points, and the possibility of film destruction increases. As a result, the strength of the obtained conductor pattern is not only reduced due to the generation of cracks, but also the bonding strength with the substrate cannot be fully ensured.
[0088] In this regard, in the metal oxide adhered silver powder of the present embodiment, a metal oxide having a melting point lower than that of silver is adhered to the surface of the silver particles. By using a conductive paste containing such a metal oxide adhered silver powder, when applied to a substrate, it is possible to suppress the uneven presence of silver and a low-melting-point metal oxide in the coating film due to their specific gravity difference. As a result, microcracks in the conductive pattern can be reduced to improve the strength, and the bonding strength between the conductive pattern and the substrate can also be improved.
[0089] The metal oxide having a melting point lower than that of silver contained in the adherend is preferably at least one of Te oxide, Bi oxide, Pb oxide, Tl oxide and V oxide. Such oxide can more reliably suppress over-sintering of silver particles, thereby further improving the strength and bonding strength of the conductive pattern. Furthermore, Te oxide and Bi oxide can further reduce the softening point temperature of the glass powder, thereby further improving the strength of the conductive pattern.
[0090] In addition, the content of the metal oxide having a melting point lower than that of silver contained in the adherend is preferably 0.01 mass % to 10 mass % relative to the silver contained in the metal oxide adhered silver powder when the adherend contains only the metal oxide. In addition, in the case where not only the first adherend containing the metal oxide but also the second adherend containing the metal component constituting the metal oxide or the alloy thereof with silver is formed, the content of the total metal component is preferably 0.1 mass % to 10 mass % relative to the silver contained in the metal oxide adhered silver powder. By setting such a content, the reduction of conductivity caused by the metal oxide can be suppressed, and the strength and bonding strength of the conductor pattern brought about by the metal oxide can be improved.
[0091] Example
[0092] Next, the present invention will be described in further detail based on Examples, but the present invention is not limited to these Examples.
[0093] <Example 1> (Preparation of Metal Oxide Adhesive Silver Powder)
[0094] First, a silver complex solution was prepared. Specifically, 3670.1 g of a silver nitrate aqueous solution having a silver concentration of 1.4% by mass was placed in a glass beaker, and 161.8 g of ammonia water having a concentration of 28% by mass (2.67 mol of ammonia per 1 mol of silver) was added to the silver nitrate aqueous solution to obtain a silver-amine complex aqueous solution.
[0095] In addition, as a reducing agent, a 21.0 mass % formaldehyde aqueous solution obtained by diluting formalin with pure water was prepared. Furthermore, when oxidation was performed, a tellurium aqueous solution was prepared as an aqueous solution containing a metal component that forms a metal oxide having a melting point lower than that of silver. 3.4 g of tellurium dioxide (tellurium dioxide powder manufactured by Wako Pure Chemical Industries, Ltd., purity 99.9%) was added to 10 g of a 20 mass % sodium hydroxide aqueous solution and 27 g of pure water to be dissolved, thereby preparing a tellurium aqueous solution.
[0096] Next, add 7.5 g of a 20% by mass sodium hydroxide aqueous solution to the prepared silver-amine complex aqueous solution and stir for 3 minutes. After that, add 357.6 g of a formaldehyde aqueous solution as a reducing agent (equivalent to 1 mol of silver) while stirring the silver-amine complex aqueous solution to reduce and precipitate the silver particles. Add a tellurium aqueous solution 5 seconds after the start of adding the reducing agent. Thus, tellurium oxide adheres to the surface of the silver particles. One minute later, add 6.01 g of a 1.55% by mass stearic acid ethanol solution to the slurry containing the silver particles to terminate the reduction reaction, stop stirring, and allow the silver particles to settle.
[0097] Next, the slurry in which the silver particles were precipitated was filtered, and the precipitate on the filter paper was washed with water until the conductivity of the washing water after the water flow was 0.2 mS / m or less, and then the precipitate was vacuum dried at 73° C. for 10 hours to obtain a dry powder. The obtained dry powder was put into a crusher (SK-10 model manufactured by Kyoritsu Riko Co., Ltd.) and crushed for 30 seconds twice to obtain the tellurium-adhered silver powder of this Example 1.
[0098] The tellurium-adhered silver powder obtained in Example 1 was subjected to the following measurements.
[0099] (EPMA analysis)
[0100] The surface and cross section of the tellurium-adhered silver powder of Example 1 were measured by magnifying them 15,000 times using an electron beam microanalyzer EPMA (device name: JXA-8200, manufactured by JEOL Ltd.). The results are shown in Figure 1 and Figure 2 . Figure 1 This is a diagram showing element mapping of the surface of the silver powder of Example 1. Figure 2 : is a diagram showing element mapping of a cross section of the silver powder of Example 1. Figure 1 and Figure 2 As shown, it can be seen that the Te component adheres to the Ag surface on the surface of the silver particle, and that the Te component adheres to the surface of the silver particle not uniformly but partially.
[0101] (Special amount)
[0102] The content of tellurium (Te) contained in the silver powder was measured. Specifically, the silver content was measured by a weight method (mass method), that is, after the tellurium-adhered silver powder was completely dissolved in nitric acid, hydrochloric acid was added to precipitate silver chloride and filtered, and the mass of the silver chloride was measured. In addition, the content of Te was measured as follows: after the tellurium-adhered silver powder was heated and dissolved in nitric acid, it was measured by inductively coupled plasma (ICP) emission spectrometry (SPS5100 manufactured by SII). As a result, it was found that the content of Te was 1.3% by mass relative to silver. It should be noted that in this measurement, the metal oxide, metal, and alloy of tellurium were all dissolved and measured, so the total amount of this metal component relative to silver was 1.3% by mass without distinguishing them.
[0103] (ESCA assay)
[0104] The state of the tellurium-adhered silver powder surface (about a few nm from the sample surface) was analyzed using ESCA (ULVAC-PHI Co., Ltd., Model 5800). Specifically, the tellurium adhering to the silver powder was determined to be in the form of an oxide, a metal element, or an alloy. The measurement conditions at this time were as follows: the analysis area was set to 800 μmφ, and the applied power was set to 150.0 W. As a result, it was found that on the surface of the tellurium-adhered silver powder, at least the metal element Te (or alloyed Te) and TeO 2 Coexistence, metallic Te (or alloyed Te) and TeO 2 The ratio of the number of Te atoms between the two is 12:7. It should be noted that in the state analysis, the state is identified based on the difference in the binding energy of the atoms, so it is impossible to determine whether it is a single substance of Te or an alloyed Te.
[0105] The total amount of the metal component relative to silver is 1.3 mass %, and therefore the content of the metal component (Te) constituting Te oxide is calculated to be 0.48 mass % relative to silver.
[0106] (Particle size distribution measurement)
[0107] The tellurium-adhered silver powder of Example 1 was subjected to a particle size distribution measurement. Specifically, 0.1 g of the tellurium-adhered silver powder was dispersed in isopropyl alcohol (IPA), stirred for 2 minutes in a cell disruptor (model: BM-4) manufactured by Nippon Seiki Co., Ltd., and then measured using a laser diffraction particle size distribution measuring device (Microtrac MT3300EXII manufactured by Nikkiso Co., Ltd.). As a result, the cumulative 10% particle size (D10) was 1.11 μm, the cumulative 50% particle size was 1.77 μm, and the cumulative 90% particle size (D90) was 2.93.
[0108] (Specific surface area measurement)
[0109] The specific surface area of the tellurium-adhered silver powder of Example 1 was measured. Specifically, a BET specific surface area measuring device (Macsorb HM-model 1210 manufactured by Mountech Co., Ltd.) was used, and Ne-N was passed through the measuring device at 60°C. 2 The mixed gas (nitrogen 30%) was degassed for 10 minutes, and then the specific surface area of the tellurium-adhered silver powder of Example 1 was measured by the BET one-point method. 2 / g.
[0110] (Preparation of Conductive Paste)
[0111] The conductive paste was prepared as follows using the tellurium-adhered silver powder of Example 1. Specifically, a total of 89.6% by mass of the tellurium-adhered silver powder of Example 1 (the amount of tellurium relative to silver was 1.3% by mass) and silver powder without a metal-containing adherent (AG-4-8F manufactured by DOWA HIGHTECH CO., LTD.), 6.2% by mass of an excipient for high-speed printing (a mixture of pine alcohol, texanol, and butyl carbitol acetate) as an organic binder, 1.0% by mass of wax (castor oil), 100 cs of dimethyl polysiloxane, and 100% by mass of ethanol were mixed with a propeller-free self-rotating and revolving stirring degassing device (AR250 manufactured by Shinki Co., Ltd.). 0.4 mass %, 0.2 mass % of triethanolamine, 0.2 mass % of oleic acid, 2.0 mass % of Pb-Te-Bi glass powder, and 0.4 mass % of solvent (mixture of pineol and texanol) were stirred at 1400 rpm for 30 seconds, and then kneaded by passing through a three-roll mill (80S manufactured by EXAKT) with a roll gap of 100 μm to 20 μm to obtain a conductive paste. The ratio of tellurium-adhered silver powder to silver powder was adjusted so that the content of tellurium became 0.015 mass % relative to the total amount of silver contained in the conductive paste.
[0112] (Formation of Conductive Pattern)
[0113] The formation of the conductive pattern is carried out as follows. First, on a silicon substrate (100Ω / □) for solar cells, a screen printer (MT-320TV manufactured by Microtech Co., Ltd.) is used to form a 154mm solid pattern on the back of the substrate using aluminum paste (Alsolar 14-7021 manufactured by Toyo Aluminum Co., Ltd.). Next, after filtering the conductive paste with a 500μm sieve, a finger electrode with a width of 27μm and four busbar electrodes with a width of 0.95mm designed on the surface side of the substrate are printed at a scraper speed of 350mm / sec. After hot air drying at 200°C for 10 minutes, a high-speed baking furnace IR furnace (NGK Insulators, Ltd., high-speed baking test 4-chamber furnace) is used to perform baking at a peak temperature of 770°C and an in-and-out time of 41 seconds to obtain a conductive pattern.
[0114] (Evaluation of Conductive Pattern)
[0115] The conductivity and adhesive strength of the conductive pattern were measured in the following manner.
[0116] The conductivity of the conductive pattern was evaluated based on the series resistance value and conversion efficiency. Specifically, the series resistance value of the conductive pattern was measured using a digital multimeter (R6551 manufactured by ADVANTEST), and the conversion efficiency was measured using a solar simulator (Wacom Denso Co., Ltd., WXS-156S-10, AM1.5G).
[0117] The adhesive strength of the conductive pattern is evaluated based on the peel strength when the conductive pattern is peeled off from the substrate. Specifically, after cutting the silicon substrate and adjusting its size to approximately 6 cm × 6 cm, the back of the substrate is pasted and fixed with double-sided tape. Next, a halogen-free non-rosin flux is applied to the busbar portion of the substrate surface with a cotton swab. Next, a soldering tape (0.9 mm wide) is placed on the busbar on a hot plate set at 50°C and the flux is applied again. A soldering iron (temperature set to 380°C) is brought into contact with the end of the soldering tape from above the soldering tape, and it is scanned to the other end in about 2 to 3 seconds for soldering. Then, a universal tensile testing machine EZ-SX (test speed: 15 mm / sec, stroke 100 mm) manufactured by Shimadzu Corporation is used to move the soldering tape in a manner of peeling it in the opposite direction of 180°, and the peel strength (180° peel strength) is measured.
[0118] (Cross-sectional evaluation of conductive pattern)
[0119] Furthermore, the cross section of the conductive pattern after firing was observed, and the distribution of Te atoms was analyzed using EPMA. The measurement was performed using an electron beam microanalyzer EPMA (device name: JXA-8200, manufactured by JEOL Ltd.) at a magnification of 3,000 times.
[0120] <Example 2>
[0121] In Example 2, a silver-amine complex aqueous solution, a formaldehyde aqueous solution, and a tellurium aqueous solution were prepared in the same manner as in Example 1. Furthermore, as a post-addition reducing agent aqueous solution, a solution prepared by adding 10.0 g of a 20% sodium hydroxide aqueous solution to 71.5 g of a 21.0% formaldehyde aqueous solution was prepared. In Example 2, after adding the formaldehyde aqueous solution and the tellurium aqueous solution to the silver-amine complex aqueous solution in the same manner as in Example 1, 10 seconds after the addition of the tellurium aqueous solution, a post-addition reducing agent aqueous solution was further added to promote reduction. Then, 1 minute later, 6.01 g of a stearic acid ethanol solution having a concentration of 1.55% by mass was added to the slurry containing the silver particles to terminate the reduction reaction, and stirring was stopped to allow the silver particles to settle. Thereafter, filtration, washing, drying, and crushing were performed in the same steps as in Example 1 to obtain the tellurium-adhered silver powder of Example 2.
[0122] The tellurium-adhered silver powder of Example 2 was measured for the tellurium (Te) content in the silver powder in the same manner as in Example 1. The tellurium (Te) content relative to silver was 3.0 mass %. In addition, ESCA measurement was performed, and it was confirmed that no metal element Te was present in the adhered material. 2 In addition, for the tellurium-adhered silver powder of Example 2, the element mapping of the adherend was performed using a field emission transmission electron microscope (HF-2200 manufactured by Hitachi High-Technologies Corporation). The results showed that the layer of the adherend was uniform, and the relationship between Ag, Te and oxygen in terms of atomic % was 1:1:2. 2 In the amorphous form. In addition, the particle size distribution was measured in the same manner as in Example 1, and the results were D10, D50, and D90, respectively, and 1.1 μm, 1.7 μm, and 2.7 μm, respectively. In addition, the specific surface area was measured in the same manner as in Example 1, and the results were 0.68 m 2 / g.
[0123] Using the silver powder of Example 2, a conductive paste and a conductor pattern were prepared in the same manner as in Example 1 and evaluated.
[0124] <Example 3>
[0125] In Example 3, the tellurium-adhered silver powder of Example 3 was obtained by performing the same operations as in Example 2 except that the amount of tellurium dioxide added was increased from 3.4 g to 5.7 g in the preparation of the tellurium aqueous solution.
[0126] The tellurium-adhered silver powder of Example 3 was measured for the tellurium (Te) content in the silver powder in the same manner as in Example 1. The tellurium (Te) content relative to silver was 3.6% by mass. In addition, ESCA measurement was performed. As in Example 2, it was confirmed that no metal single substance Te was present in the adhered material. 2 In addition, it is predicted that Ag and TeO in the adhesion 2 In the amorphous form. In addition, the particle size distribution was measured in the same manner as in Example 1, and the results were D10, D50, and D90, respectively, and 1.1 μm, 1.7 μm, and 2.7 μm, respectively. In addition, the specific surface area was measured in the same manner as in Example 1, and the results were 0.68 m 2 / g.
[0127] Using the silver powder of Example 3, a conductive paste and a conductor pattern were prepared in the same manner as in Example 1 and evaluated.
[0128] <Example 4>
[0129] In Example 4, the same operation as in Example 2 was performed except that a bismuth aqueous solution was used instead of a tellurium aqueous solution to prepare the bismuth-adhered silver powder of Example 4. The bismuth aqueous solution was prepared by adding and dissolving 4.367 g of bismuth nitrate pentahydrate (bismuth nitrate pentahydrate produced by Wako Pure Chemical Industries, Ltd., purity>99.5%) in 10 g of a 20 mass % sodium hydroxide aqueous solution.
[0130] The surface and cross section of the bismuth-adhered silver powder of Example 4 were measured by EPMA in the same manner as in Example 1. Figure 3 and Figure 4 result. Figure 3 3 is a diagram showing element mapping of the surface of the silver powder of Example 4. Figure 4 : is a diagram showing element mapping of a cross section of the silver powder of Example 4. Figure 3 and Figure 4 As shown, it can be seen that the Bi component adheres to the Ag surface on the surface of the silver particles, and that the Bi component adheres to the surface of the silver particles not uniformly but partially.
[0131] The bismuth-adhered silver powder of Example 4 was measured for bismuth (Bi) in the silver powder in the same manner as in Example 1. The result showed that the content of bismuth (Bi) relative to silver was 3.0% by mass. In addition, ESCA measurement was performed, and it was confirmed that no metallic single substance Bi was present in the adhered material. 2 O 3The particle size distribution was measured in the same manner as in Example 1, and the results were D10, D50, and D90, respectively, and 1.3 μm, 1.9 μm, and 2.9 μm, respectively. The specific surface area was measured in the same manner as in Example 1, and the results were 0.60 m 2 / g.
[0132] Using the silver powder of Example 4, a conductive paste and a conductor pattern were prepared in the same manner as in Example 1 and evaluated.
[0133] <Comparative Example 1>
[0134] In Comparative Example 1, a conductive paste was prepared and evaluated in the same manner as in Example 1 except that tellurium-adhering silver powder was not used and only silver powder without an adherent material containing a metal was added.
[0135] <Comparative Example 2>
[0136] In Comparative Example 2, a conductive paste was prepared and evaluated in the same manner as in Example 1 except that metal tellurium powder (99.9% purity, manufactured by Kojundo Chemical Laboratory Co., Ltd.) was mixed instead of tellurium-adhered silver powder so that the tellurium content was 0.015 mass % relative to the total amount of silver contained in the conductive paste.
[0137] <Comparative Example 3>
[0138] In Comparative Example 3, a conductive paste was prepared and evaluated in the same manner as in Example 1 except that tellurium dioxide powder (Wako Pure Chemical Industries, Ltd., tellurium dioxide powder, purity 99.9%) was mixed instead of tellurium-adhered silver powder so that the tellurium content was 0.015 mass % relative to the total amount of silver contained in the conductive paste.
[0139] <Evaluation Results>
[0140] The evaluation results of the examples and comparative examples are shown in the following Tables 1 and 2. Table 1 summarizes the specific surface area, particle size distribution, and amount of silver relative to the adherend of the silver powder of Examples 1 to 4, as well as the state analysis of the adherend using ESCA. It should be noted that in Table 1, the specific surface area and particle size distribution of the silver powder without adherend ("AG-4-8F" manufactured by DOWA HIGHTECH CO., LTD.) are recorded for comparison with the silver powder of Examples 1 to 4 to which metal oxides, etc. are adhered. In addition, in Table 2, the conversion efficiency, series resistance, and peel strength of each conductor pattern produced using the silver powder of Examples 1 to 4 and Comparative Examples 1 to 3 are summarized.
[0141] [Table 1]
[0142]
[0143] As shown in Table 1, the amount of metal components contained in the adherends of the silver powders of Examples 1 to 4 having tellurium or bismuth adherends was within the range of 0.1 mass % or more and 10 mass % or less relative to silver. It was also confirmed that the silver powders of Examples 1 to 4 having adherends had a larger specific surface area than the silver powder (AG-4-8F) having no adherends.
[0144] [Table 2]
[0145]
[0146] As shown in Table 2, according to Examples 1 to 3 in which tellurium-attached silver powder was added to the conductive paste, and Example 4 in which bismuth-attached silver powder was added, it was confirmed that the peel strength could be improved while maintaining the conversion efficiency, compared with Comparative Example 1 containing only silver powder without an adherent containing a metal oxide. In addition, according to Example 1, it was confirmed that not only the series resistance value could be reduced and the conversion efficiency could be improved, but also the peel strength could be greatly improved, compared with Comparative Example 2 in which metal tellurium powder and silver powder were added, and Comparative Example 3 in which tellurium dioxide powder and silver powder were added.
[0147] In addition, the cross sections of the conductor patterns in Example 1, Comparative Example 2, and Comparative Example 3 were observed by EPMA, and the results showed that Figure 5 Results shown. Figure 5 1 is a diagram showing element mapping of the cross section of each conductor pattern of Example 1, Comparative Example 2, and Comparative Example 3. Figure 5 In the embodiment, it is confirmed that a conductive pattern (blue: mainly silver) containing voids (black) is formed on a substrate (dark blue), and Te components (water color ~ yellow-green ~ yellow) are distributed in the conductive pattern. Specifically, compared with Example 1, in Comparative Examples 2 and 3, a large number of parts with a high probability of Te existence (yellow-green ~ yellow) can be seen, and it can be seen that the Te component is unevenly present. In addition, it can be seen that as in Example 1, by using silver powder having an adherent containing a metal oxide having a melting point lower than silver on the surface of the silver particles, a conductive pattern in which the metal components constituting the metal oxide are moderately dispersed is obtained. As a result, it can be seen that the conductive pattern can obtain a high bonding strength.
[0148] As described above, by allowing the oxide of a metal component with a lower melting point than silver to adhere to the surface of silver particles, when the conductive paste is sintered to form a conductive pattern, the uneven presence of silver and the metal component with a low melting point in the thickness direction can be suppressed, thereby improving the bonding strength while maintaining the conductivity of the conductive pattern at a higher level.
Claims
1. A silver powder comprising: silver particles; and an adherent adhered to the surface of the silver particles, The adherend includes a first adherend or includes a first adherend and a second adherend, the first adherend is a metal oxide having a melting point lower than that of silver, and the second adherend is a metal formed of a metal component constituting the metal oxide or an alloy of the metal component and silver, The metal oxide is at least one of Te oxide, Bi oxide, Pb oxide, Tl oxide and V oxide, The volume-based cumulative 50% particle size of the silver powder is 0.5 μm to 4 μm, The manufacturing method of the silver powder is: adding a reducing agent and an aqueous solution containing the metal component constituting the metal oxide having a melting point lower than that of the silver to the silver complex solution, The silver particles are reduced and precipitated, and the metal oxide of the metal component is precipitated and adhered on the surface of the silver particles, or the metal oxide and the metal formed by the metal component constituting the metal oxide or the alloy of the metal component and silver are precipitated and adhered on the surface of the silver particles.
2. The silver powder according to claim 1, wherein The content of the metal component constituting the metal oxide is 0.01 mass % to 10 mass % based on silver.
3. The silver powder according to claim 1, wherein The metal component is at least one of Te, Bi, Pb, Tl, and V.
4. The silver powder according to any one of claims 1 to 3, wherein The total amount of the metal components other than silver constituting the metal oxide in the adhered material is 0.1% by mass to 10% by mass based on silver.
5. A method for producing the silver powder according to claim 1, comprising the steps of: adding a reducing agent and an aqueous solution containing the metal component constituting the metal oxide having a melting point lower than that of the silver to a silver complex solution, The silver particles are reduced and precipitated, and the metal oxide of the metal component is precipitated and adhered on the surface of the silver particles, or the metal oxide and the metal formed by the metal component constituting the metal oxide or the alloy of the metal component and silver are precipitated and adhered on the surface of the silver particles. 6 . A conductive paste comprising: the silver powder according to claim 1 ; the silver powder having no adherent matter containing metal on the surface; an organic binder; glass powder; and a solvent.
7. The conductive paste according to claim 6, wherein The content of the metal component constituting the metal oxide contained in the silver powder according to any one of claims 1 to 4 is 0.001 mass % to 0.03 mass % based on the silver contained in the conductive paste.
Citation Information
Patent Citations
Conductive paste for solar battery, solar battery and manufacturing method therefor, and solar battery module
JP2018190967A
Conductive paste for formation of a solar cell element electrode, solar cell element, and manufacturing method for said solar cell element
WO2010016186A1
Wiring board manufacturing method
JP1997232727A
Silver powder for conductive paste, its manufacturing method, and conductive paste using the same
JP2004079211A
Silver compound-coated silver powder and production method therefor
JP2005298933A